Combination of Chemo- and Biocatalysis: Conversion of Biomethane to Methanol and Formic Acid - Benny Kunkel; Dominik Seeburg; Tim Peppel; Matthias Stier; Sebastian Wohlrab (Applied Sciences, 2019)
In the present day, methanol is mainly produced from methane via reforming processes, but research focuses on alternative production routes. Herein, we present a chemo-/biocatalytic oxidation cascade as a novel process to currently available methods. Starting from synthetic biogas, in the first step methane was oxidized to formaldehyde over a mesoporous VOx/SBA-15 catalyst. In the second step, the produced formaldehyde was disproportionated enzymatically towards methanol and formic acid in equimolar ratio by formaldehyde dismutase (FDM) obtained from Pseudomonas putida. Two processing routes were demonstrated: (a) batch wise operation using free formaldehyde dismutase after accumulating formaldehyde from the first step and (b) continuous operation with immobilized enzymes. Remarkably, the chemo-/biocatalytic oxidation cascades generate methanol in much higher productivity compared to methane monooxygenase (MMO) which, however, directly converts methane. Moreover, production steps for the generation of formic acid were reduced from four to two stages.